Artificial fertilisation and early development of a limpet Lottia tenuisculpta (Patellogastropoda: Lottiidae). (2nd January 2020) - Nakano, Tomoyuki; Nakayama, Ryo; Takahashi, Yoko
ABSTRACT: Patellogastropoda is an ecologically widely diversified group living on various substrata. Juveniles of Lottia tenuisculpta live on rocks and also on the shell of trochid snails, from which host they are thought to derive some benefit. Generally, selective settlement on suitable habitats is one of the most important factors for increasing its growth and survival rates. However, the cue(s) for settlement to specific substrata have been less studied. To prepare for future investigations of settlement, we conducted experiments using described protocols to find the most efficient methods of artificial fertilisation and laboratory culture for L. tenuisculpta . We conducted all described methods of inducing spawning: thermal shocking; hydrogen peroxide treatment; desiccation; ultraviolet irradiation of seawater; bubbling of air; gamete stripping and alkaline maturing. Dissection of male gonads was the most efficient method of collecting sperm and dropping sperm onto mature females was the best method to stimulate egg release. The early development of L. tenuisculpta is mostly identical to other species of Lottia . The larvae settled at the bottom of containers about 96 hours after fertilisation. Adult shells began to grow at 7–8 days and reached 1 mm in length about 50 days after fertilisation.